2022
DOI: 10.3389/fpsyg.2021.772093
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Creativity on the Relationship Between Mathematic Achievement and Programming Self-Efficacy

Abstract: Purpose: This study aimed to explore the relationship between mathematic achievement and programming self-efficacy, and adopt a mediation model to verify the mediating role of creativity on the relationship between mathematic achievement and programming self-efficacy.Methods: A total of 950 upper-secondary school students were surveyed using their math test scores, the Kirton Adaption-Innovation and the Programmed Self-Efficacy Scale. SPSS-26 was used for descriptive statistical analysis and correlation analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 77 publications
0
5
0
1
Order By: Relevance
“…A quantitative survey of 211 students at a large-scale public higher education institution in Southeastern America found that there was a positive association between personal innovative ability in information technology and self-efficacy in using computers in different environments (Thatcher and Perrewe, 2002). Further evidence also showed that innovation was positively related to students' self-efficacy in programming (Liu et al, 2022) and the professional self-efficacy of undergraduate nursing students (Shen et al, 2021).…”
Section: Self-efficacymentioning
confidence: 99%
“…A quantitative survey of 211 students at a large-scale public higher education institution in Southeastern America found that there was a positive association between personal innovative ability in information technology and self-efficacy in using computers in different environments (Thatcher and Perrewe, 2002). Further evidence also showed that innovation was positively related to students' self-efficacy in programming (Liu et al, 2022) and the professional self-efficacy of undergraduate nursing students (Shen et al, 2021).…”
Section: Self-efficacymentioning
confidence: 99%
“…In recent years, studies on the relationship between self-efficacy and academic achievements has gradually permeated into different academic disciplines. For instance, studies on mathematics show that effective feedback and mathematics self-efficacy significantly affect academic achievements in mathematics [31]. Similarly, studies on language disciplines demonstrate that students with high academic self-efficacy outperform those with low self-efficacy in reading achievements [32].…”
Section: Geographical Self-efficacy and Academic Achievements In Geog...mentioning
confidence: 99%
“…Programming learning is crucial for creativity and innovation. Individuals with solid programming skills, even if not software developers, can understand the digital environment and solve problems in many areas of life (Liu et al, 2022;Su et al, 2022).…”
Section: Introductionmentioning
confidence: 99%